Aspects of Sharia Legal Maqashid Syariah and Qawaidul Fiqhiyyahin Property Finance in Sharia Housing Cases - Meliana Murti Prakastiwi (Universitas Muhammadiyah Surakarta, 2024)
In meeting the need for housing, low-income people find it very difficult to own a house with cash. The development product was originally a conventional product, namely KPR, but in sharia banking the system used is profit sharing/margin so it is without usury. The focus of this paper discusses how maqashid sharia and qawaidul fiqhiyyah review sharia mortgages which are currently one of the favorite products in sharia banking. The author uses a normative juridical method, namely research law using secondary data sources. Normative, because this research will examine secondary data starting from a review of maqashid sharia and qawaidul fiqhiyyah in the field of sharia banking, especially sharia mortgages. Operationally, normative juridical research is carried out by library research facilities. The results of this research are that sharia mortgages are permitted because they are part of the implementation of sharia objectives or maqashid sharia in terms of protecting family and property. Likewise, it is also assessed that home ownership is a basic need for every human being, that with the existence of sharia mortgages it can provide benefits for Muslims in general, according to qawaidul fiqhiyyah contracts in sharia mortgages are permissible by referring to several fiqh rules.